Man and Machine in Macroeconomics - Kevin D. Hoover (Duke University, Center for the History of Political Economy (CHOPE), 2012)
The potted histories of macroeconomics textbooks are typically Keynes-centric. Keynes is credited with founding macroeconomics, and the central developments in the field through the early 1970s, including large-scale macroeconometric models are usually termed "Keynesian." The story of macroeconomics is framed as support or opposition (e.g., monetarism or the new classical macroeconomics) to Keynes. The real story is more complicated and involves at least two distinct threads. Keynes was important, but perhaps more important for the detailed development of the field were the early macroeconometricians – Ragnar Frisch and Jan Tinbergen. Frisch and Tinbergen adopted physical or mechanical metaphors in which aggregate quantities are central. Keynes's vision of macroeconomics is better described as "medical." It is based in human psychology and individual decision-making and sees the economy as an organic system. Whereas policymakers and economic advisers in Keynes view can operate only within the economic system, Frisch and Tinbergen laid the basis for an optimal-control approach to economic policy in which the policymaker stands outside the system. Recent new classical macroeconomics has adopted an uneasy amalgam of the medical and mechanical metaphors.
Keywords: B22; B23; 330; macroeconomics; Keynes; Frisch; Tinbergen; Klein; macroeconometric models; macroeconomic policy